Features of computation of energy efficiency indicators on basis of statistical accounting of Ukraine - Ruban-Maksimets O.O. (General Energy Institute of the National Academy of Sciences of Ukraine, 2009)
The problem of increasing of energy efficiency is considered and classification of energy efficiency indexes is presented. The generalized methods of determination of efficiency indexes of using the fuel and energy resources on basis of statistical accounting of Ukraine are presented.